WIN 52035-2 inhibits both attachment and eclipse of human rhinovirus 14. - Shepard, D A (1993)
WIN compounds inhibit attachment of human rhinovirus 14 by binding to a hydrophobic pocket within the capsid and inducing conformational changes in the canyon floor, the region that binds the cellular receptor. To study the basis of drug resistance, we isolated and characterized a family of human rhinovirus 14 mutants resistant to WIN 52035-2. Thermostabilization data and single-cycle growth curves provided evidence for two classes of resistant mutants. One class, here called exclusion mutants, showed a marked decrease in drug-binding affinity and was characterized by substitution to bulkier amino acid side chains at two sites lining the hydrophobic pocket. The other class, called compensation mutants, displayed single-amino-acid substitutions in the drug-deformable regions of the canyon; these mutants were able to attach to cells despite the presence of bound drug. A delay in the rise period of the growth curves of compensation mutants indicated a second locus of drug action. WIN 52035-2 was found to inhibit the first step of uncoating, release of VP4. Attempts to identify this site of drug action by using single-step growth curves were obscured by abortive elution of a major fraction of cell-attached virus. The drug had no effect on the rate of this process but did affect the spectrum of particles produced.